2020
DOI: 10.1007/s00062-020-00956-5
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Automated Attenuation Measurements at Identifying Large Vessel Occlusion Stroke on CT Angiography

Abstract: Purpose Computed tomography angiography (CTA) is routinely used to detect large-vessel occlusion (LVO) in patients with suspected acute ischemic stroke; however, visual analysis is time consuming and prone to error. To evaluate solutions to support imaging triage, we tested performance of automated analysis of CTA source images (CTASI) at identifying patients with LVO. Methods Stroke patients with LVO were selected from a prospectively acquired cohort. A control group was selected from consecutive patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In order to provide a full analysis of the capabilities of our algorithm while increasing comparability to previous studies [5][6][7][8][9][10]14,16,[24][25][26][27][28][29][30][31][32][33][34] , the evaluation of the models was divided into (i) object-level and (ii) patient-level evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to provide a full analysis of the capabilities of our algorithm while increasing comparability to previous studies [5][6][7][8][9][10]14,16,[24][25][26][27][28][29][30][31][32][33][34] , the evaluation of the models was divided into (i) object-level and (ii) patient-level evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have found that improving stroke workflow metrics are associated with improved clinical outcomes 15,16 and rate of reperfusion. 17 The use of AI in stroke imaging is an area of active investigation due to the potential for improving diagnostic accuracy, [21][22][23][24][25][26][27] improving outcomes by decreasing time to clinical treatment, 15,16,26 and predicting clinical outcomes. 31,[41][42][43] Given that improvement in time to treatment is associated with improved rate of reperfusion and functional outcomes, these techniques may have high clinical utility, especially in hub/spoke healthcare systems without 24-hour neuroendovascular coverage at most sites.…”
Section: Discussionmentioning
confidence: 99%
“…20 Subsequently, iSchemaView along with other providers have developed new automated techniques for detecting anterior circulation LVO by quantifying relative vessel density in the MCA territory (compared to the contralateral side), including RAPID-CTA (iSchemaView, Menlo Park, California, USA) and Viz.LVO (Viz.ai, San Francisco, California, USA). Many of the studies examining the results of these automated techniques were based on retrospective analyses of datasets from the thrombectomy trials with some patients selected from the general population at academic CSCs; [21][22][23][24][25][26][27] the techniques demonstrated relatively high accuracy, with good results in sensitivity, specificity, negative predictive value (NPV), and positive predictive value (PPV) in that patient population. Few studies looked at their effects on stroke workflow metrics, 26 such as door-togroin puncture or computed tomography angiography (CTA)-to-groin puncture times.…”
Section: Background and Significancementioning
confidence: 99%
“…Firstly, Hidlay et al ( 44) used a smartphone-based evaluation of scans for detecting LVO, with sensitivity and specificity of 100% across 80 LVO patients, in a retrospective multicentre study. Next, automated attenuation analysis was trialled by Reidler et al (45) with sensitivity values between 91 and 96% and specificity values between 77 and 83%, for a specificity cutoff of ≥0.70 when applied to their cohort of patients (79 with LVO) (45). The CT-defined hyperdense arterial sign marker for LVO demonstrated reasonably high sensitivity (67%) and specificity (82%) for identifying LVO in ischaemic stroke patients on thin and thick NCCT serial images (48).…”
Section: Imaging and Physiological Monitoring Methodsmentioning
confidence: 99%